LEGAL PROTECTION OF PATIENTS AGAINST DEFAMATION CONVICTIONS - Wilvridus Watu; Fernando Silalahi; John Pieris (Jurnal Scientia, 2023)
The state is responsible for providing proper health services as stipulated in the 1945 Constitution of the Unitary State of the Republic of Indonesia, the government as the personification of the state is obliged to provide legal protection to patients. The protection in question is that the state explicitly establishes special laws for patients. Healthcare providers must be criminally responsible if there are mistakes and/or negligence in providing their services that cause the patient to experience harm, both physically and non-physically. Legal regulations that have been used as instruments to protect patient rights are considered ineffective because the ethical process for health care providers, in this case, doctors, takes a protracted time, so patients have already been convicted because they were accused of committing defamation, so it becomes a dilemma for patients to take legal steps against doctors who have committed malpractice and harmed patients. This study uses normative legal research methods with statutory approaches, legal concept approaches, and qualitative approaches to describe and produce descriptive data. The results of this study indicate that until now, there has been no regulation that specifically regulates the rights of patients so it is the state's responsibility for proper health services and should form special laws to protect the rights of patients.